Analisis Makna Kesulitan dan Kemudahan Surat Al-Syarh â€œKajian Semiotika Al-Qurâ€™anâ€ - Zulaika, Zulaika; Vahlepi, Sahrizal (Universitas Batanghari Jambi, 2023)
Humans are equipped with reason so that they can analyze all the miracles of the Qur'an, then activate this mind optimally by analyzing several theories in order to achieve a goal and its intended meaning. Every individual certainly has various obstacles and obstacles in wading through life, not apart from the ease and difficulty. Sometimes not all conveniences go easily and forever, as well as difficulties. Then the question arises whether in every difficulty there will be ease? And if you want to get convenience, do you have to go through difficulties first? and is it certain that every difficulty will be rewarded with ease in this world or in the here after? Some of these questions become separate problems that require definite and accurate answers. Among the approaches in studying the meaning of the Qur'an related to the problem mentioned above is semiotics which is a study in terms of literature or language, which has developed since the time of ancient Greece. Language is a very important object in life, which is a tool for communication and transactions. Therefore, this article tries to analyze the relationship of meaning with difficulty and ease through a language or semiotic approach. This approach was chosen as a means of exploring broader and deeper meanings related to the meanings of difficulty and ease. For data collection the authors use library research techniques (library research). Published written data are in the form of books, journals, articles and books of classical and contemporary interpretations that are relevant in this study. The discussion of writing is carried out using an analytic descriptive method to explain the meaning and interpretation of the verses of the Qur'an broadly and explain a new meaning about the relationship of the meaning of difficulty and ease of Surah al-Insyirah. And in conclusion this verse contains a lesson in terms of morality where we are told to be patient, optimistic and always put our trust in Allah. The meaning of difficulty and ease can change according to the word that goes with it.